Strategi Pemasaran Batik Tulis Djanur Aryosuno Berbasis Pemberdayaan Ekonomi Lokal melalui Analisis SWOT di Desa Karang Anyar, Kecamatan Ketapang, Kabupaten Sampang - Rizal Rizal; Fadllan Fadllan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research is motivated by the development of batik in the current sampang district which should be Djanor Aryosuno Boutique determine the marketing strategy used. the main purpose of determining the strategy so that DJA Boutique can objectively see the internal and external conditions of the company in an effort to compete with other batik. The purpose of this study is how the marketing strategy of Batik Djanor Aryosuno in Ketapang Sampang. Furthermore, how the application of swot analysis as a marketing strategy at Batik Djanor Aryosuno in Ketapang Sampang. This research uses a qualitative approach with a case study design to analyze the marketing strategy of Batik Tulis Djanur Aryosuno based on local economic empowerment through SWOT analysis. Data were collected through observation, interviews, documentation, and literature study, with the subjects selected purposively. The analysis process includes data reduction, verification, and data presentation, then analyzed descriptively to describe the real conditions in the field. The results of the study show that Batik Djanor Aryosuno has the strengths of product, resources, management, profit, capital and good cooperation. The weaknesses are the lack of assertiveness of experts, technology, competitors and promotion. Opportunities include cooperation and customer trust, while the threat is the many creative competitors in the field of producing batik.